ENHANCING AWARENESS OF ILLEGAL COSMETIC HAZARDS THROUGH TARGETED EDUCATION IN A VOCATIONAL HEALTH SCHOOL - Irma Susanti; Amalia Dwiyanis Ruhmana; Fathin Dliyaun Nisa' Ali; Denes Yulfa Fatma Aisyah; Nur' Aini Izza Susanti (Journal of Community Research and Engagement, 2026)
Background: Cosmetics are one of the most commonly encountered pharmaceutical products used daily by people of all ages, from babies to adults. With the rapid expansion of the beauty industry and e-commerce markets, the circulation of unregistered and hazardous beauty products has risen significantly, posing a serious public health threat. Objective: This community service activity was conducted at SMK Kesehatan Insan Bhakti Husada Lamongan to assess and enhance students’ knowledge regarding the dangers of illegal cosmetics. Vocational health students represent a crucial demographic, as they serve as future health advocates in their communities. Method: The method used in this activity is an interactive lecture method with evaluation through pre-test and post-test questionnaires. Results: The results show an average knowledge increase of 11.99%. The highest average increase was found in the question about types of heavy metals whose contamination levels are regulated by BPOM, with the average score rising from 22.72% in the pre-test to 90.90% in the post-test, demonstrating that targeted educational interventions can effectively eliminate critical knowledge gaps regarding regulatory safety standards. Conclusion: This community service activity successfully heightened students' awareness, proving that early educational outreach is a vital strategy for preventing the health risks associated with unauthorized cosmetic products.